Implementasi Bi’ah Lughawiyyah Guna Meningkatkan Kemampuan Berbicara di Ma’had Aly Baitul Qur’an Putri Wonogiri - Safira Azizatush Sholihah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2025)
The purpose of this study is to implement the bi'ah lughawiyyah program in Ma'had Aly, analyze the results of the program implementation, the impact of the program implementation on the skills of students, as well as the advantages and disadvantages of this program. The research method used is a descriptive qualitative method using data collection techniques that include participatory observation, structured interviews, and documentation. The results of this study are the implementation of the bi'ah lughawiyyah program in the form of Arabic vocabulary enrichment activities; muhadatsah practice; and so on. The impact of this activity is that students are getting used to using Arabic in everyday communication. The advantages of this program are that students are expected to understand the contents of the Qur'an and As-Sunnah as well as books that are scientific references that mostly use Arabic, also to train students' public speaking, increase self-confidence and increase linguistic insight in students. While the disadvantages of this study are the lack of enthusiasm and awareness in students to speak using Arabic, as well as differences in abilities between students in regular and takhassus classes.